Soluble human leukocyte antigen-G evaluation in pregnant women with gestational diabetes mellitus - Muhamad R. Abdel Hameed; Osama Ahmed Ibrahiem; Entsar Hamed Ahmed; Paula Rofaeel Sedky; Naglaa Mohamed M. A. Mousa (SpringerOpen, 2020)
Abstract Background Gestational diabetes mellitus is any degree of glucose intolerance with onset or first recognition occurring late in second trimester and third trimester of pregnancy. It constitutes a greater impact on diabetes epidemic as it carries a major risk for developing type 2 diabetes mellitus to the mother and her fetus later in life. human leukocyte antigen (HLA)-G is a class Ib gene presents in the human major histocompatibility complex (MHC). HLA-G has an important role for mother and fetus tolerance during pregnancy, also in the pancreatic islet cells protection. This is a case-control study, measuring serum HLA-G levels by ELISA in 60 pregnant women with gestational diabetes compared with 36 normal pregnant women. Results HLA-G levels were significantly high in pregnant women with gestational diabetes mellitus (GDM) in contrast to women with normal pregnancy (P = 0.001). Conclusion Women with GDM had significantly higher levels of soluble HLA-G than women without GDM, suggesting that HLA-G molecule is among the factors for regulation and control of the immune response and the induction of tolerance. Soluble HLA-G could be considered an important follow-up investigation for all pregnant primary health care for early detection of gestational diabetes.